Controlling phase transformation during milling in the pre-formulation of Active pharmaceutical Ingredients - Ghaidaa Sulaiman Hameed (College of Pharmacy / Mustansiriyah University, 2019)
A high percentage of active pharmaceutical ingredient are available in the insoluble crystalline phase.  During pharmaceutical processing such as milling there are many issues can be initiated due to the transformation of this crystalline materials. Some trans-formation might be positively solving the active pharmaceutical ingredients (APIs) problems such as solubility and dissolution rate while others might negatively affect these factors which render the APIs into inactive compound. Therefore, during the pre-formulation study, all of these issues must be resolved to ensure drug stability and hence its bioavailability. This review will shed the light on the most popular transformations that happened, factors affecting them, and the characterization methods used for the detection of phase formed. The studying of these factors, will help to avoid them in future